The spaces we work in: consultation about Curtin's Architecture and Planning building - MacCallum, Diana; Khan, Shahed (La Trobe University, 2012)
In 2009, Curtin University made an in-principle commitment to a ‘re-life’ project for Building 201, which houses its School of Built Environment. The project, Build 201.1, was to represent a major overhaul of the building’s space, which has been subject to ad hoc incremental, sometimes desperate and often disjointed changes to cope with changing demands through its forty-year history. In November 2011, the School took the highly unusual step of holding a stakeholder forum to identify user concerns and needs and, thus, inform the project definition statement (which will form the basis of a detailed budget and tender documents). In this paper we, as the organisers of that forum, reflect on its process and outcomes, in relation not only to the physical space we work in but – equally crucially – to the spaces of governance and communication that shape our institutional environment. This reflection is informed by responses from 20 of the forum’s 52 participants (students, academics, general staff and sessional tutors) to a post-event questionnaire, which sought to determine how various actors saw the process represented by the forum and how they reflect on their experience of engagement in it.